(untitled) (A+BE | Architecture and the Built Environment, 2025)
This research is a component of the 2ALL Addis Ababa Living Lab project, which focuses on creating resilient dwelling clusters for urban resettlement in Addis Ababa, Ethiopia. Funded by NWO-WOTRO, the project explores innovative housing approaches aligned with the overarching Sustainable Development Goal (SDG) of building sustainable cities and communities. Reconstructing Dwelling examines dwelling culture in relation to housing conditions within both planned and unplanned neighbourhoods of Addis Ababa. Ethnographic methods are employed to study housing practices across various housing development models, focusing on layers of dweller-initiated housing transformations to uncover patterns of habitation. The study also conducts a comparative analysis of the temporalities that are present in the adaptations made by residents. These transformations are visually reconstructed and documented through ethnographic surveys, culminating in a pattern catalogue to identify and redefine key socio-spatial patterns that shape the culture of dwelling in Addis Ababa: The gibi, gwaro and gwada. Rooted in the principles of alternative epistemologies, the study emphasises these patterns as critical elements informing dwelling design. It reveals the links between these patterns and dweller-initiated transformations, showcasing their essential role in space-making. Consequently, the research contributes to rethinking architectural pedagogy, practice, and policy in a more contextually grounded and inclusive manner. By situating itself within contemporary challenges, Reconstructing Dwelling builds a body of knowledge aimed at developing inclusive and resilient dwelling clusters. This approach offers an alternative to the current disruptive resettlement practices in Addis Ababa, which often undermine livelihoods and disregard existing socio-spatial patterns.